Adaptive Leadership In The Digital Era In Educational Institutions - Maulana, Irwan; Sirajuddin, Sirajuddin; Susanti, Rahayu; Sari, Eliana; Karnati, Neti (Annpublisher, 2024)
This study aims to describe adaptive leadership in educational institutions in the digital era. This research uses a literature study method by observing various kinds of documents, both from books and journals. The literature study focuses on researching literature related to adaptive leadership in the digital era. Data collection is carried out by collecting literature data, reading, recording, and managing research results objectively, systematically, analytically, and critically by looking at the year of publication and the most up-to-date research. The result of this study is that adaptive leadership is needed so that educational institutions are able to adapt and encourage change to their subordinates. Adaptive leadership requires agile awareness to read and respond to future changes